Acetylation of PhoP K88 Is Involved in Regulating Salmonella Virulence - Li, Jianhui (Infect Immun, 2021)
The PhoP-PhoQ two-component regulation system of Salmonella enterica serovar Typhimurium is involved in the response to various environmental stresses and is essential for bacterial virulence. Our previous studies showed that acetylation plays an important role in regulating the activity of PhoP, which consequently mediates the change in virulence of S. Typhimurium. Here, we demonstrate that a conserved lysine residue, K88, is crucial for the function of PhoP and its acetylation-downregulated PhoP activities. K88 could be specifically acetylated by acetyl phosphate (AcP), and the acetylation level of K88 decreased significantly after phagocytosis of S. Typhimurium by macrophages. Acetylation of K88 inhibited PhoP dimerization and DNA-binding abilities. In addition, mutation of K88 to glutamine, mimicking the acetylated form, dramatically attenuated intestinal inflammation and systemic infection of S. Typhimurium in the mouse model. These findings indicate that nonenzymatic acetylation of PhoP by AcP is a fine-tuned mechanism for the virulence of S. Typhimurium and highlights that virulence and metabolism in the host are closely linked.